The Restructuring of Human Resource Management (HRM) Through the "Intranet" as Part of ICT: A Case Study in Internal Communication in Cameroonians Banks - Sonkeng, Germain; Nguezet, Paul Martin Dontsop; Tidjani, Bassirou (Prabandhan: Indian Journal of Management, 2012)
The objective of the present paper is to study the impact of the Intranet on internal communication in organizations, with specific reference to Cameroonian Banks. The study highlights the changes brought about by the ''Intranet'' in internal communication in the sample banks. The theoretical study focuses on concepts and previous studies done by other researchers on the stakes of Intranet in communication. The empirical study follows a methodology that presents sample cases and analysis. Using interviews and questionnaires, the researchers collected facts and analyzed them. The results of the study revealed that the Intranet makes internal communication more transparent, increases its speed and makes administrative management procedure lighter on the one hand, but on the other hand, despite the many advantages of the Intranet, traditional means of communication are not so obsolete and they are still being widely used as a means of communication in organizations.